2011
DOI: 10.1021/cm103548t
|View full text |Cite
|
Sign up to set email alerts
|

Counterion Dynamics in Polyurethane-Carboxylate Ionomers with Ionic Liquid Counterions

Abstract: Polyurethane carboxylate ionomers based on poly(ethylene glycol) (M n = 600) with sodium and various ammonium, phosphonium and imidazolium cations are synthesized for systematic comparison of different cationic counterions. Generally, larger cations act as plasticizers, lowering T g because of weaker Coulombic force for ion associations (acting as physical cross-links). T g can be reduced from 47 °C to -6 °C when replacing Na þ with large ether-oxygen containing ammonium without changing polymer composition an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
128
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(138 citation statements)
references
References 54 publications
6
128
1
Order By: Relevance
“…They proposed that higher fractional free volumes depressed the Vogel temperature, T 0 , allowing for ion mobility at temperatures signifi cantly below T g . Colby and co-workers [ 14 ] studied the introduction of mobile imidazolium countercations to polymers containing pendant carboxylate groups. Colby and coworkers [ 14 ] concluded that T g does not completely dominate the ionic conductivities, and segmental relaxation of polymer chains correlated strongly with ionic conductivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They proposed that higher fractional free volumes depressed the Vogel temperature, T 0 , allowing for ion mobility at temperatures signifi cantly below T g . Colby and co-workers [ 14 ] studied the introduction of mobile imidazolium countercations to polymers containing pendant carboxylate groups. Colby and coworkers [ 14 ] concluded that T g does not completely dominate the ionic conductivities, and segmental relaxation of polymer chains correlated strongly with ionic conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Colby and co-workers [ 14 ] studied the introduction of mobile imidazolium countercations to polymers containing pendant carboxylate groups. Colby and coworkers [ 14 ] concluded that T g does not completely dominate the ionic conductivities, and segmental relaxation of polymer chains correlated strongly with ionic conductivity. They also revealed that the increased size of the countercation reduced T g and increased the concentration of nontrapped or mobile ions.…”
Section: Introductionmentioning
confidence: 99%
“…The increased efficiency of phosphonium versus ammonium polycations was ascribed to their efficient cationic charge distribution (centered on the phosphorus atom, while distributed through adjacent carbons on the ammonium moiety), as demonstrated by calculations, 21,22 which lead to stronger and more stable interactions with the negatively charged nucleic acids.…”
Section: Introductionmentioning
confidence: 95%
“…24 Importantly, different partial charges and charge distributions have been suggested, where for phosphonium ions the positive charge is centered at the P atom, whereas in the ammonium group is comparatively more distributed through the adjacent carbons, resulting in a weaker cationic charge in the ammonium groups. 21,25 Consequently, in quaternary ammonium moieties the adjacent hydrogen atoms (α-and β-methylene hydrogens) are also more positively charged, which results in stronger hydrogen bonding, further shortening contact distances with their anionic counterions.…”
Section: Phosphonium Versus Ammonium Cations: Similarities Differencmentioning
confidence: 99%
“…Being less electronegative than the adjacent carbons, the phosphorus atom of nBu4P + carries a positive charge (+1.1e) leaving the outer atoms to share (-0.1e). 25 This partially negative shell surrounding the cationic P atom in turn provides a partial shielding which weakens the coulombic interaction with anionic counterions. Conversely, being more electronegative that the bound carbon atoms, in n-Bu4N + nitrogen carries a negative charge (-0.5e) leaving the outer atoms to share (+1.5 e), which results in higher attraction towards anions.…”
mentioning
confidence: 99%